Literasi Pengelolaan Dan Keuangan Usaha Desa Lolomoyo Tuhemberua Kecamatan Gunungsitoli Barat Kota Gunungsitoli - Dian Septiana Sari (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The aim of this service is to increase public understanding and knowledge in carrying out business development literacy and financial planning. Then it is also hoped that the community will be able to optimize business opportunities properly so that business needs are fulfilled and family welfare is achieved. Lolomoyo Tuhemberua Village, located in Nias Regency, is a village located in a tourism area with 80% of the people working as farmers and business actors. The low level of welfare is mainly due to low income and poor consumption patterns. The plan for this service activity will be carried out for 2 days starting from field observations to counseling with the theme of efforts to improve understanding of financial planning properly and correctly. business and financial management properly and correctly, for example: 1) calculating the cost of goods sold, 2) recording/booking every transaction; 3) make simple financial reports (manual recording); and 4) implementing very practical financial software.